Wind Erosion Potential Influenced by Tillage in an Irrigated Potato–Sweet Corn Rotation in the Columbia Basin - Sharratt, B. S.; Collins, H. P. (Agronomy journal, 2018)
Core Ideas Irrigated agricultural lands in the Columbia Basin are highly susceptible to wind erosion.Alternatives to conventional tillage practices are needed to reduce wind erosion.Wind erosion potential was lower for reduced than conventional tillage practices.Wind erosion was most apparent after potato harvest in a potato–corn–corn rotation.Managing cover crops and tillage are key to minimizing wind erosion. Wind erosion is a concern within the Columbia Basin of the US Inland Pacific Northwest (PNW) due to soils being sandy and retaining little residue after harvest of vegetable crops like potato. This study assessed potential wind erosion of a 3‐yr irrigated potato (Solanum tuberosum L. ‘Ranger Russet’)–sweet corn (Zea mays L. ‘Triple Super Sweet’)–sweet corn rotation subject to conventional and reduced tillage. Sediment flux was measured inside a portable wind tunnel after primary tillage of potato in autumn 2009 and sowing potato and sweet corn in spring 2010. Soil and crop residue characteristics that influence wind erosion were measured concurrently with sediment flux. Soil loss differed among crops in autumn 2009 and between tillage treatments in spring 2010. Soil loss was greater from potato (approached 1 Mg ha−1 min−1) than first or second year corn (approached 0.1 Mg ha−1 min−1) and from conventional (approached 1 Mg ha−1 min−1) than reduced tillage (approached 0.3 Mg ha−1 min−1). Simulations by the Wind Erosion Prediction System (WEPS) showed most of the erosion over the 3‐yr rotation occurred after harvest of potato in September to the following March. Differences in soil loss among crop treatments or between tillage practices were likely due to differences in residue cover and/or silhouette area. Since wind erosion was most apparent after harvest of potato and from conventional tillage, cover crops should be established soon after harvest and reduced tillage practices adopted to protect the soil from wind erosion in the Columbia Basin.